1995
DOI: 10.1007/bf00032252
|View full text |Cite
|
Sign up to set email alerts
|

Research evaluation and impact analysis of biological nitrogen fixation

Abstract: IntroductionLimited adoption of inoculation technology Assessment of "need to-inoculate" Abstract Although viable Rhizobium inoculation technology for cultivated legumes has long been available, there has been little sustained adoption of this technology in tropical regions. Reasons contributing to this include inadequate demonstration of the technology, presence of adequate native rhizobia, high soil mineral nitrogen levels which suppress nitrogen fixation, inadequate quality control of Rhizobium inoculum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The potential components of the agricultural research and development system include institutions such as governmental extension system, governmental agricultural research organisations, international agricultural research organisations, universities, non-governmental organisations, producer federations and community-based organisations that have a role in agricultural or rural development, as well as the models and approaches that these institutions use to increase crop productivity, build soil fertility, raise farm incomes and improve the nutritional status of farming families (Abate et al , 2011; Ajayi et al , 2007; Bantilan and Johansen, 1995, Chianu et al , 2011; Mhango et al , 2013; Nyemeck Binam et al , 2011; Shelton et al , 2005; Snapp et al , 2002a; Spielman et al , 2011; Wambugu et al , 2011).…”
Section: Review Of Adoption Studiesmentioning
confidence: 99%
“…The potential components of the agricultural research and development system include institutions such as governmental extension system, governmental agricultural research organisations, international agricultural research organisations, universities, non-governmental organisations, producer federations and community-based organisations that have a role in agricultural or rural development, as well as the models and approaches that these institutions use to increase crop productivity, build soil fertility, raise farm incomes and improve the nutritional status of farming families (Abate et al , 2011; Ajayi et al , 2007; Bantilan and Johansen, 1995, Chianu et al , 2011; Mhango et al , 2013; Nyemeck Binam et al , 2011; Shelton et al , 2005; Snapp et al , 2002a; Spielman et al , 2011; Wambugu et al , 2011).…”
Section: Review Of Adoption Studiesmentioning
confidence: 99%
“…Bantilan et al (1995) reported that rhizobium inoculum technique is not often successful in the tropics as a result of inadequate demonstration of the technology, presence of adequate native rhizobia, high soil mineral nitrogen level which suppresses N fixation, inadequate quality control of rhizobium inocula and difficulty in inoculation under tropical conditions. In order to proffer solution to this problem, it is imperative to identify indigenous rhizobial strains that are effective in N fixation.…”
Section: Introductionmentioning
confidence: 98%